OPTIMALISASI POTENSI SUMBER DAYA PETANI UNTUK PEMELIHARAAN SAPI POTONG RAKYAT PADA BASIS PERTANIAN BERBEDA DI SUMATERA BARAT - Asdi Agustar; James Hellyward; Mardiati Zein (Udayana University, 2015)
Beef cattle raising have been doing as sideline business in farming systems. Such conditions lead to frequent farmers are not fully paying attention. Therefore, the potential for increased economic value is very likely obtained when competencies resource owned by the farmers can be utilized optimally. The study aims to map the the resource owned by the farmers in particular the potential of land, feed resouces and family labour. The study was conducted at three (3) areas with different agricultural commodity basis, using the survey with 180 respondent randomly selected. The results shown that farmers at the smallholders estate area have more resources than both farners in the crop and horticulture basis areas. In all three areas of research, utilization of resoources are still not optimal. Optimizing the use of available resources is still possible to increase the scale of beef cattle raising in the three areas of research.